An Online Multistep-Forward Voltage-Prediction Approach Based on an LSTM-TD Model and KF Algorithm. - Ni, Ye; Xia, Zhilong; Zhao, Fangtong; Fang, Chunrong; Chen, Zhenyu (Computer (00189162), 2021)
We propose a multistep-forward voltage-prediction approach combining a long short-term memory time-distributed model and the Kalman filter algorithm to improve prediction efficiency and reduce the demand for computing capability.